Embriogênese somática, melhoramento da resposta in vitro e transformação de milho (Zea may L.) via Agrobacterium tumefaciens - Silva, Marilia Rodrigues de (2009)
Plant genetic engineering opens new perspective in obtaining superior maize (Zea mays L.) genotypes. Agrobacterium tumefaciens transformation has been the preferred method for this purpose and for that the tissues culture is a requirement. However, maize is considered the most in vitro culture and genetic transformation recalcitrant crop. The critical points for Agrobacterium tumefaciens mediate transformation refer to the use of in vitro responsive genotypes, type of explants used to initiate embryogenic culture and protocols well adjusted for the transfer of T-DNA by the Agrobacterium tumefaciens. This study aimed (1) to evaluate leaf explants to accelerate the embryogenic callus obtaining process, (2) to develop hybrids by crossing two in vitro responding inbred lines to improve capacity of embryogenic callus inducing, and (3) evaluate the transfer of T-DNA by infection of embryogenic calli and immature tassel segments with Agrobacterium tumefaciens. The experiments were developed in the of Plant Biotechnology, Bacteriology and Virology Laboratories at FAMV/UPF. To evaluate the leaf explants four selected genotypes (L20, HS1, HS2 and V4), and the explants immature tassel segments, basal leaves from in vitro seedlings and leaves of plants with 6-7 weeks were cultivated on three different calli induction media based on N6 medium. In this experiment it was possible to conclude that maize leaf segments have low potential for somatic embryogenesis in the genotypes tested, not overcoming the immature tassel. For the breeding in vitro response, two inbred lines (L2 and L20) with high production of embryogenic calli were used in reciprocal crosses producing the F1 hybrids H3MT-1 (L2 x L20) and H3MT-2 (L20 XL2). Immature tassels of the inbred lines and hybrids were evaluated in vitro. The maize hybrids did not surpass the L20 parent line in the production of embryogenic callus. However, the use of hybrid plants is advantageous because simple hybrids show hybrid vigor when compared to homozygous lines. To evaluate the T-DNA transfer into maize, immature tassels and embryogenic calli of different genotypes were infected with the EHA105 strain of Agrobacterium tumefaciens carrying the pCambia 3301 plasmid, which contains the gus reporter gene and the bar marker gene using the Vega et al. (2008) based protocol. The T-DNA transfer was evaluated by the GUS histochemical assay. The two explants control (not infected with Agrobacterium tumefaciens) showed background (expression of a gus-like gene). The tassel of H3MT-1 hybrid and embryogenic calli of L2 inbred line showed higher intensity of blue color compared to their respective controls suggesting the T-DNA transference